(untitled) (TAJ: Journal of Teachers Association, 2009)
Chordoma is very rare bony tumour which arises from the notochordal remnants .Nine cases of Chordoma in the nasopharynx were identified in Rajshahi Medical College Hospital since January 1997 to December 2009. All the patients were non-diabetic and 2 of them were hypertensive. Their renal function tests and liver function tests were normal. TAJ 2009; 22(1): 295-297